Activity-dependent synaptic competition and dendrite pruning in developing mitral cells - Imai, Takeshi (Frontiers in Neural Circuits, 2025)
During the early postnatal period, neurons in sensory circuits dynamically remodel their connectivity to acquire discrete receptive fields. Neuronal activity is thought to play a central role in circuit remodeling during this period: Neuronal activity stabilizes some synaptic connections while eliminating others. Synaptic competition plays a central role in the binary choice between stabilization and elimination. While activity-dependent “punishment signals” propagating from winner to loser synapses have been hypothesized to drive synapse elimination, their exact nature has remained elusive. In this review, I summarize recent studies in mouse mitral cells that explain how only one dendrite is stabilized while others are eliminated, based on early postnatal spontaneous activity in the olfactory bulb. I discuss how the hypothetical punishment signals act on loser but not winner dendrites to establish only one primary dendrite per mitral cell, the anatomical basis for the odorant receptor-specific parallel information processing in the olfactory bulb.